Choroidal thickness using EDI-OCT in adult-onset vitelliform macular dystrophy. Issue 1 (December 2016) - Palácios, Renato; Mendes, Thaís; Sano, Ronaldo; Wu, Davi; Aihara, Teruo; Almeida Manzano, Roberta
Abstract Background To compare choroidal thickness in patients with adult-onset foveomacular vitelliform dystrophy (AOFVD) with healthy subjects and to correlate choroidal thickness with age, gender and spherical equivalent. Methods A prospective, observational study of 37 eyes (15 eyes in AOFVD group and 22 eyes in control group) was conducted. Images were acquired by enhanced depth imaging optical coherence tomography (EDI-OCT). Choroidal thickness measurements were performed in the subfoveal region and at 500, 1000 and 1500 µm intervals from the foveal center to nasal and to temporal regions for subsequent averaging of values. Results The AOFVD group consisted of four male eyes (28.6 %) and 10 female eyes (71.4 %); age was 33–62 years; spherical equivalent (SE) ranged from −1.50 to 1.50 spherical diopters (SD); mean subfoveal thickness was 325.6 µm, ranging from 186 to 420 µm; and the average of thicknesses was 309.4 µm, ranging from 188 to 413 µm. The control group consisted of 12 male eyes (54.5 %) and 10 female eyes (45.5 %); age was 27–62 years; SE ranged from −2.50 to 0.50 SD; subfoveal thickness was 294.8 µm, ranging from 213 to 481 µm; and the average of thicknesses was 279.4 µm, ranging from 201 to 458 µm. Conclusions The AOFVD group and the control group showed similar choroidal thickness by correcting for age, SE and gender. Not yet known, completely, which biochemical and vascular flow alterations of the choroid, and which functional RPE changes may play a role in the pathogenesis of this disease. EDI-OCT, incorporated in some SD-OCT devices, allows higher quality assessment of the choroid. In this article, choroidal thickness of patients with AOFVD, a rare disease with a not fully understood pathogenesis, was assessed.